Odpowiedzi

Najlepsza Odpowiedź!
2010-02-17T23:13:59+01:00
(√81-√64)*√5 1/16=...
= ( 9 -8)*√(81/16)=
= 1*(√81) : √(16)=
= 9 : 4=
= 9/4=
= 2¼
√1,21+√3 1/16 / √2,56-√1 9/16=...
= √(121/100) + √(49/16) / √(256/100) - √(25/16)=
= (11/10) + [(7/4 ) : (16/10 )]-( 5/4) =
= (11/10) +[ (7/4)*(10/16)] - (5/4) =
= (11/10) + 70/64 -(5/4) =
= (11/10 ) + (70/64) - (80/64)=
= (11/10) - (10/64) =
= ( 352/320) - ( 50/320)=
= 302/320

(5√0,09-3√0,04)*(2√2 ¼-3√1 7/9)=...
= [5√(9/100) - 3√( 4/100)]*[ 2√(9/4) -3√(16/9)]=
= [ 5*(3/10) - 3*(2/10)] *[ 2*(3/2) - 3*(4/3)]=
= [ (5/10 ) - (6/10)] *[ 3 - 4] =
= (-1/10)*(-1)=
= 1/10

∛3 3/8*∛0,125:(∛64:∛8/27)=...
=∛(27/8)∛(125/1000) : [ 4 : (2/3)]=
= (3/2)*(5/10) : [ 4*(3/2)] =
= (3/2)*(1/2) : [ 6] =
= (3/4)*(1/6)=
= 1/8